2010
DOI: 10.4049/jimmunol.0901572
|View full text |Cite
|
Sign up to set email alerts
|

The Association of MHC Class I Proteins with the 2B4 Receptor Inhibits Self-Killing of Human NK Cells

Abstract: The killing activity of NK cells is carried out by several activating NK receptors, which includes NKp46, NKp44, NKp30, NKp80, NKG2D, and 2B4. The ligands of these receptors are either self-derived, pathogen-derived, stress-induced ligands or tumor ligands. Importantly, none of these killer ligands are expressed on NK cells and thus self-killing of NK cells is prevented. A notable exception with this regard, is the ligand of the 2B4 receptor. This unusual receptor can exert both activating and inhibiting signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 40 publications
0
10
1
Order By: Relevance
“…Betser-Cohen et al recently found HLA I proteins coimmunoprecipitate with anti-NKp44 antibodies; reciprocally, NKp44 coimmunoprecipitates with anti-β-2-microglobulin antibodies [17]. Additionally, the Nef protein of HIV prevents surface expression of the activating NKp44 ligand on CD4 infected T cells, which is also consistent with the ability of Nef to retain HLA I intracellularly [18], [19].…”
Section: Introductionmentioning
confidence: 62%
“…Betser-Cohen et al recently found HLA I proteins coimmunoprecipitate with anti-NKp44 antibodies; reciprocally, NKp44 coimmunoprecipitates with anti-β-2-microglobulin antibodies [17]. Additionally, the Nef protein of HIV prevents surface expression of the activating NKp44 ligand on CD4 infected T cells, which is also consistent with the ability of Nef to retain HLA I intracellularly [18], [19].…”
Section: Introductionmentioning
confidence: 62%
“…Instead, it appeared to be tightly controlled by MHC class I in human NK cells [21] and by collective and simultaneous engagement of other NK receptors, e.g., LFA-1 and NKG2D [22,23]. Thus, human NK cells are protected from autologous lysis by 2B4 via at least 2 mechanisms: suppression of 2B4 by MHC class I and cross-talk among other receptors.…”
Section: Discussionmentioning
confidence: 88%
“…The RCDII lines also had higher expression levels of SH2 domain containing 1B (SH2D1B/EAT-2) which can act as an adapter molecule for the cell surface receptors CD84, CD244 and CD150 (SLAMF1) 27. All RCDII cell lines expressed CD244 (table 1), a receptor expressed by NK cells and effector/memory T cells,28 while SLAMF1 expression was downregulated in the RCDII cell lines. In addition, several other genes that are associated with T-cell mediated immunity according to the PANTHER classification were downregulated in the RCDII lines compared with the T-cell lines, in particular granulysin (GNLY), lymphotoxin β (LTB) and tumour necrosis factor receptor 4 (figure 1A,B).…”
Section: Resultsmentioning
confidence: 99%